Translating the Poet - Russell Scott Valentino ([sic])
You want your author to be appreciated, to be read. Yes, why not, to be respected. As a writer at least, if not as a person. And the author’s image, not just the work, is in your hands. That’s the way it works in English at least, where translation tends to be decentralized. I’m not referring to commissions obviously. In that sense translation is like any kind of creative writing – you choose your project, you shape it, you develop it, you pitch and promote it, and you pitch and promote the image of the author that goes with it. So the question: what to do when your author is not an especially attractive character, not a good person, a bad husband, for instance, a bad father?For instance, Eligio Zanini was a bad husband and a bad father. He abandoned his family when two children were small and a third was on the way. He never contacted them again, though he lived just down the road. When his son died in a car accident at the age of seventeen and the parents were supposed to go down to Split to retrieve the body, he didn’t show up, though the boy’s mother, Bianca, held out hope until the last minute. She was devastated by her husband’s departure and carried the wound as if fresh inside her.